X-linked inhibitor of apoptosis protein accelerates migration by inducing epithelial–mesenchymal transition through TGF-β signaling pathway in esophageal cancer cells - Yuxiang Jin; Xinye Lu; Mingdong Wang; Xuewei Zhao; Lei Xue (Cell & Bioscience, 2019)
Abstract Background The prognosis of esophageal cancer is still dismal because of its high probability of metastasis that is likely related to the cellular process of epithelial–mesenchymal transition (EMT). Recent studies have shown a novel role of X-linked inhibitor of apoptosis protein (XIAP) in regulating the migration process of cancer cells and, therefore, linking to progression and poor prognosis of cancer. Methods The expression of XIAP in esophageal squamous cell cancer (ESCC) tissues was determined by immunohistochemistry assay. Cell migration was analyzed by wound healing assay and Transwell assay. The expression of EMT markers (E-cadherin, N-cadherin and Vimentin) was revealed by immunofluorescence assay. Quantitative real‑time PCR analysis and Western blot analysis were used to detect the expression of XIAP and EMT markers as well as transforming growth factor-β (TGF-β) at mRNA and protein level, respectively. Results We found that the expression of XIAP closely correlated to the probability of lymphatic metastasis in patients and that ESCC patients with the high XIAP expression were associated with worse overall survival (OS). Univariate and multivariate analysis also revealed XIAP as an independent prognostic factor for overall survival in ESCC patients. In both EC9706 and TE13 cell lines, knockdown of XIAP decreased the migration of cancer cells by inhibiting EMT process through regulating the TGF-β signaling pathway, pinpointing a regulatory role of XIAP in migratory process upon TGF-β activation. Conclusions Taken together, our results suggest XIAP as a important prognostic and regulative factor in ESCC patients. XIAP may promote migration of esophageal cancer cells through the activation of TGF-β mediated EMT.